Aktivitas Fisik dan Persepsi Manfaat Kesehatan pada Wanita Usia Produktif di Kecamatan Rungkut Surabaya: Studi Mixed Methods - Amelia Lorensia; Cynthia Marisca Muntu; Krisyanti Budipramana; Marthy Meliana Ariyanti Jalmav; I Nyoman Yoga Diputra (IJMT : Indonesian Journal of Midwifery Today, 2026)
Background: Physical activity among women of productive age plays an important role in maintaining physical and mental health as well as preventing non-communicable diseases. Objective: This study aimed to analyze physical activity patterns and perceptions regarding the health benefits of physical activity among women of productive age. Methods: This study employed a mixed-methods approach using a convergent parallel design. The quantitative phase used a cross-sectional approach, while the qualitative phase applied interpretative phenomenological analysis (IPA). The study involved women aged 18–45 years living in Rungkut District, Surabaya. A total of 130 respondents participated in the quantitative phase using purposive sampling, while 20 respondents were involved in in-depth interviews during the qualitative phase. Physical activity was measured using a modified International Physical Activity Questionnaire (IPAQ). The questionnaire validity and reliability tests showed valid items with Cronbach’s alpha value of 0.84. Results: The results showed that most respondents frequently engaged in physical activity (73.18%) with predominantly light-intensity activities (56.92%). Respondents generally understood the health benefits of physical activity, including maintaining muscle health, controlling blood pressure, improving sleep quality, and maintaining mood stability. Chi-square analysis showed no significant relationship between the frequency of physical activity and respondents’ perceptions of health benefits (p>0.05). Qualitative findings revealed that respondents perceived daily activities such as house cleaning, walking, exercise, and yoga as forms of physical activity. Time constraints, fatigue, and busy daily schedules were identified as barriers to regular exercise. Conclusion: Most women of productive age demonstrated good awareness regarding the health benefits of physical activity, although this awareness was not significantly associated with the frequency of physical activity performed.